Application of gas wettability alteration to improve methane drainage performance: A case study - Jia, Lin; Li, Kewen; Shi, Xiaohong; Zhao, Lipeng; Linghu, Jianshe (International journal of mining science and technology, 2021)
Hydraulic fracturing technique is widely used for methane drainage and has achieved good effects in numerous coal mines, but negative effects may occur as the fracturing fluids are absorbed into the coal seam. Gas wettability alteration (GWA) technology can be used as it can enhance the gas and water mobility during dewatering process as a result of capillary pressure change. However, there have been few reported field tests in coal mines using GWA technology. This paper describes a pilot-scale field test in Xinjing coal mine, Yangquan, China. The fluorocarbon surfactants perfluorooctyl methacrylate monomer-containing polymethacrylate (PMP) was used to alter the wettability of coal seam to strong gas-wetness during the hydraulic fracturing process. The study focuses on the comparison of two boreholes (Boreholes #9 and #10) and one other borehole (Borehole #8) with and without using GWA approach. A well-defined monitoring program was established by measuring the dewatering volume of the fracturing fluid and the drainage volume of methane as well as the concentration. The field test results showed that the average methane drainage rates of Boreholes #9 (39.28 m3/d) and #10 (51.04 m3/d) with GWA treatment exceeded that of Borehole #8 (21.09 m3/d) without GWA treatment, with an increase of 86.3% and 142.1%, respectively. The average methane concentrations of Boreholes #9 (4.05%) and #10 (6.18%) were 64.6% and 151.2% higher than that of Borehole #8 (2.46%), respectively. On the other hand, the dewatering ratio of Boreholes #9 (4.36%) and #10 (3.11%) was almost 19 times and 13 times greater than that of Borehole #8 (0.22%). These field test results were in agreement with the experimental data. The significant increase in both methane concentration and dewatering ratio demonstrated that GWA technology could be applied for enhanced methane drainage in coal mines. Important lessons learned at Xinjing coal mine might be applied to other coal mines in China and elsewhere.